(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
The study concerned the embryonic development of spinal cord of white choeked bulbul Pycnonotus leucotis. The spinal cord at the age 40 hour’s incubation from the neural tube and its tissue wall is composed of two layers, the ependymal layer and mantle layer. The spinal cord differentiation is completed at the age 7 day’s incubation, its, were we notice that the central canal is clear and cavity lined with neurons and we note the arrangement of gray matter in the form of the letter H and its inside and it is characterized by dorsal and ventral horns and the gray matter substance and note the formation of dorsal medium spetum and ventral medium fissure.